PERAN PARISADA HINDU DHARMA INDONESIA DI KABUPATEN PESAWARAN DALAM PEMBINAAN UMAT (STUDI KASUS DI DESA PUJODADI LAMPUNG) - Untung Suhardi, Ni Putu Citra Nasih, I Wayan Arif Sugiyarta, I Made Biasa (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2019)
The phenomenon of social change is the beginning of the emergence of an event of socio-religious change that occurred in the village of Pujodadi where the dominant factor is the marriage factor. In terms of responding to the problem of social-religious change, PHDI Pesawaran District plays a role in fostering Hindus and carrying out a role in overcoming the problem of social change in a study. There are two identification problems, namely the extent to which the role of PHDI in Pesawaran District is in overcoming the phenomenon of religious conversion among Hindus and is there a relationship between the PHDI work program in Pesawaran District in the case of conversion in Pujodadi Village. This research is qualitative research with the descriptive method, with interview data collection techniques. The results showed that the role of PHDI in Pesawaran District in fostering the ummah was only limited to guiding by using the discourse dharma method and the number of religious conversion perpetrators continued to increase in the last five years due to PHDI Districts that did not have long-term work programs or short-term work programs. So that the work program related to the case of conversion is still not maximal. Keywords: Perubahan Sosial, Peran PHDI, Pengembangan Masyarakat